Gama-Lactones from Iryanthera species - Vieira, Paulo C.; Yoshida, Massayoshi; Gottlieb, Otto R.; Filho, Hipólito F.Paulino [UNESP]; Nagem, Tanus J.; Filho, Raimundo Braz (Elsevier B.V., 1983)
The structure of juruenolide, a constituent of Iryanthera juruensis and I. ulei is revised to (2S, 3R, 4S)-3-hydroxy-4-methyl-2-(19′-piperonyl-1′-n-nonadecyl)-butanolide. The compound is epimeric at C-3 of the γ-lactone unit with grandinolide [(2S, 3S, 4S)-3-hydroxy-4-methyl-2- (19′-phenyl-1′-n-nonadecyl)-butanolide] from I. grandis. An extract of I. juruensis contained additionally juruenolide-B [(4S)-4-methyl-2-(19′-piperonyl-1′-n-nonadec-7′-enyl)-but-2-enolide]. Analogous products with heptadecyl and pentadecyl side chains co-occur with the respective nonadecyl derivatives. © 1983.
Keywords: 2-(ω-aryl-n-alkyl)-γ-lactones.; grandinolide; I. juruensis; I. ulei; Iryanthera grandis; juruenolides; Myristicaceae